Pengaruh Gender, Self Efficacy, Financial Knowledge dan Uang Saku terhadap Pengelolaan Keuangan Pribadi pada Mahasiswa di Kabupaten Jember - Iqbal Bagus Satria Insani; Eko Budi Satoto; Bayu Wijayantini (Universitas Nusantara PGRI Kediri, 2025)
Personal finance is an important aspect for students to achieve financial stability. This study aims to analyze the influence of gender, self-efficacy, financial knowledge, and pocket money on personal finance in college students in Jember. This study uses quantitative research methods and uses questionnaire survey techniques on 100 students from various universities. The data collection tool was a questionnaire and the analysis was conducted using multiple linear regression analysis. The results showed that self-efficacy and financial knowledge have a significant influence on student financial management, while gender and pocket money do not have a significant influence on student financial management. This indicates that self-efficacy and financial understanding are more decisive than demographic factors and the amount of money received. This study suggests the need for applicable financial education to improve students' financial literacy and confidence in managing their finances. Other variables such as financial attitudes and social influence can be investigated in the future.